2019
DOI: 10.1016/j.mex.2019.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity study of UV/ZnO treated solution containing Reactive blue 29 using Daphnia magna as a biological indicator

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…According to Khan and Malik (2018), textile dyes and the breakdown products of certain dyes like Malachite green (Zhou et al, 2019) are carcinogenic and have been linked to various diseases in plants, animals, and humans. This toxicity effect can last for a long period of time since most dyes are made up of stable aromatic compounds; thus, they are resistant to biodegradation (Dehghani et al, 2019). In a study performed by Gita et al (2019) Triphenylmethane dyes such as methyl violet (MV) and brilliant green (BG) are reported to cause gastrointestinal tract and respiratory problems in humans.…”
Section: Textile Dyesmentioning
confidence: 99%
“…According to Khan and Malik (2018), textile dyes and the breakdown products of certain dyes like Malachite green (Zhou et al, 2019) are carcinogenic and have been linked to various diseases in plants, animals, and humans. This toxicity effect can last for a long period of time since most dyes are made up of stable aromatic compounds; thus, they are resistant to biodegradation (Dehghani et al, 2019). In a study performed by Gita et al (2019) Triphenylmethane dyes such as methyl violet (MV) and brilliant green (BG) are reported to cause gastrointestinal tract and respiratory problems in humans.…”
Section: Textile Dyesmentioning
confidence: 99%
“…Consequently, recalcitrant compounds, such as polyvinyl alcohol, reactive dyes, dispersive dyes, aromatic amines, and amino‐naphthalene‐sulfonic acids, are usually present in the dyeing wastewater (Q. Chen et al, 2021; Sen et al, 2019). These dyes have stable chemical structures, which makes them resistant to micro‐biodegradation (Dehghani et al, 2019). Among different classes of dyes, ~60% of them belong to azo group (Dai et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al, 2021;Sen et al, 2019). These dyes have stable chemical structures, which makes them resistant to micro-biodegradation (Dehghani et al, 2019). Among different classes of dyes, $60% of them belong to azo group (Dai et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies compared the catalytic activity of ZnO and TiO 2 for the degradation of sulfamethazine and chloramphenicol, respectively, and reported that ZnO was slightly more effective than TiO 2 [22,23]. e performance mechanism of these processes is that the semiconductor material is irradiated with ultraviolet radiation which stimulates the electron from the valence band to the conduction band causing the release of radical hydroxyl [24,25]. According to the studies conducted so far, no report on trifluralin removal using two methods simultaneously including UV/S 2 O 8 2− and UV/ZnO processes have been reported.…”
Section: Introductionmentioning
confidence: 99%